2019
DOI: 10.1136/bmjopen-2018-022686
|View full text |Cite
|
Sign up to set email alerts
|

The economics of physical activity in low-income and middle-income countries: protocol for a systematic review

Abstract: IntroductionEvidence on the economic costs of physical inactivity and the cost-effectiveness of physical activity interventions in low-income and middle-income countries (LMICs) is sparse, and fragmented where they are available. This is the first review aimed to summarise available evidence on economics of physical activity in LMICs, identify potential target variables for policy, and identify and report gaps in the current knowledge on economics of physical activity in LMICs.Methods and analysisPeer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Study protocol with detailed methods of this review was published prior to the commencement of this review 15 and is shown in online supplemental file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Study protocol with detailed methods of this review was published prior to the commencement of this review 15 and is shown in online supplemental file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…3 It is estimated that NCDs account for 80% of the global burden of disease in LMICs and insufficient physical activity (PA) is a key contributor for premature mortality in these populations. 4 In India, an LMIC with a population of 1.4 billion people, less than 54.4% of the population meets the recommended PA guidelines and incidence rates for diabetes, heart disease and cancer are on a steep rise. [5][6][7] NCDs currently account for 53% of the disease burden and 44% of disabilityadjusted life years (DALYs) lost in India.…”
Section: Introductionmentioning
confidence: 99%